The clan records : five stories of Korea - Kajiyama, Toshiyuki, 1930-1975 (Book collections on Project MUSE., 1995)
Although little known in the West, Kajiyama Toshiyuki was one of Japan's most prolific and popular writers. Celebrated for his crisp, fast-paced style and incisive analysis, Kajiyama's popularity may be attributed to his finely tuned sense of what many Japanese felt but could not articulate: the feeling of irreplaceable loss that lay beneath post-World War II Japan's highly successful economic recovery.